Quality Analysis Of Geopolymer Concrete With Rice Husk Ash And Coffee Grounds Ash Additives - Veranita Veranita; Joli Supardi; Risna Iftah (Akademi Komunitas Negeri Aceh Barat, 2026)
Abstract:Rigid pavement is a type of road pavement that uses concrete as the primary material, with cement as the binding agent. However, the increasing use of cement in construction raises environmental concerns due to its contribution to carbon dioxide emissions. Geopolymer concrete offers an environmentally friendly alternative by using materials other than cement. This study aims to investigate the effect of adding rice husk ash and coffee grounds as additives on the compressive strength of geopolymer concrete for rigid pavements. This experimental research was conducted in a laboratory, referring to the compressive strength testing method based on SNI 1974:2011 and the mix design based on SNI DT-91-0008-2007. A total of 16 cylindrical specimens were produced with variations in the aggregate-to-binder ratio: 75:25 (normal), 75:25, 70:30, and 65:35. Each variation consisted of two specimens. The activators used were a combination of sodium silicate (Na₂SiO₃) and sodium hydroxide (NaOH) with two ratios: 3:1 and 5:2. The results showed that two specimens met the target compressive strength of 19.3 MPa (equivalent to grade K-225), with the highest strength reaching 20.67 MPa at an activator ratio of 5:2. It can be concluded that the addition of rice husk ash and coffee grounds as additives in geopolymer concrete can improve compressive strength, particularly in mixtures with an activator ratio of 5:2, compared to normal geopolymer concrete.Keywords:Coffee grounds; compressive strength ; fly ash; geopolymer concrete; rice husk ashAbstrakRigid pavement adalah jenis perkerasan jalan yang menggunakan beton sebagai bahan utama, dengan semen sebagai bahan pengikat. Namun, peningkatan penggunaan semen dalam konstruksi menimbulkan kekhawatiran lingkungan karena kontribusinya terhadap emisi karbon dioksida. Beton geopolimer menawarkan alternatif ramah lingkungan dengan menggunakan bahan selain semen. Penelitian ini bertujuan untuk mengkaji pengaruh penambahan abu sekam padi dan ampas kopi sebagai bahan tambahan terhadap kuat tekan beton geopolimer untuk perkerasan kaku. Penelitian eksperimental ini dilakukan di laboratorium dengan metode pengujian kuat tekan berdasarkan SNI 1974:2011 dan rancangan campuran berdasarkan SNI DT-91-0008-2007. Sebanyak 16 spesimen silinder dibuat dengan variasi perbandingan agregat terhadap bahan pengikat: 75:25 (normal), 75:25, 70:30, dan 65:35, masing-masing dua spesimen, serta menggunakan aktivator campuran natrium silikat (Na₂SiO₃) dan natrium hidroksida (NaOH) dengan rasio 3:1 dan 5:2. Hasil menunjukkan dua spesimen memenuhi target kuat tekan 19,3 MPa (setara kelas K-225), dengan kuat tekan tertinggi 20,67 MPa pada rasio aktivator 5:2. Kesimpulannya, penambahan abu sekam padi dan ampas kopi sebagai bahan tambahan pada beton geopolimer dapat meningkatkan kuat tekan, terutama pada campuran dengan rasio aktivator 5:2 dibandingkan beton geopolimer normal. Kata Kunci:Abu ampas kopi; beton geopolymer; fly ash; kuat tekan